Metastatic malignant melanoma of unknown primary site to the brain: A case report. (September 2021) - Mremi, Alex; Goodluck, Gregory; Sadiq, Adnan; Lodhia, Jay
Abstract: Introduction and importance: The natural history of metastatic melanoma in the absence of a known primary site has been poorly defined. The disease usually presents a significant cause of morbidity and mortality. Around 90% of melanomas have cutaneous origin, but still there are melanomas that could be found in visceral organs or lymph nodes with unknown primary site. Spontaneous regression of the primary site could be an explanation. The disease is frequently diagnosed after treatment for known extracranial metastases and has a poor outcome despite various local and systemic therapeutic approaches. Case presentation: Herein, we present a case of a 43-year old female presented with history of headaches and enlarged a left inguinal lymph node. Notably, no cutaneous lesions could be identified by history or on physical examination. CT-scan of the brain revealed a space occupying lesion and the inguinal lymph node biopsy confirmed the diagnosis of metastatic malignant melanoma. The patient succumbed shortly after establishment of diagnosis. Clinical discussion: Most patients with brain metastases from malignant melanoma are diagnosed after treatment for known extracranial metastases and have a poor outcome despite various local and systemic therapeutic approaches. Conclusion: Metastatic melanomas of brain with unknown primary present a significant morbidity and mortality and confer a poor prognosis. Delay in diagnosis and treatment is of serious concern when it comes to improve the prognosis of patients with this disease. The optimal treatment depends on the objective situation, often surgery, radiosurgery, whole brain radiotherapy and chemotherapy can be used in combination to obtain longer remissions and optimal symptom relieve. Highlights: Aggressive tumor whose pathogenesis is poorly understood. Presents metastatically without an identifiable primary lesion. Treatment guidelines for these patients are not clear-cut. Poor outcome despite various local and systemic therapies. Promising new agents and approaches are needed